2008
DOI: 10.1002/ca.20720
|View full text |Cite
|
Sign up to set email alerts
|

Surgical exposures for distal humerus fractures: A review

Abstract: The majority of distal humerus fractures have complex fracture patterns, with displaced articular segments, requiring operative intervention. The goals of surgery are anatomic reduction and rigid internal fixation via an operative approach that balances maximum required exposure with minimum soft tissue or bony disruption that may necessitate postoperative protection. The selection of a surgical approach depends on multiple factors, including, fracture pattern, extent of articular involvement, associated soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 62 publications
(94 reference statements)
0
14
0
4
Order By: Relevance
“…An adequate exposure of the distal humeral articular surface is required during surgery to treat fractures of the intercondylar humerus [5,18,25]. In our study, an examination of traverse sections of the distal triceps brachii revealed that the vessels and nerves that innervate the anconeus run downward in the triceps brachii and are relatively far from the intramuscular tendon.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…An adequate exposure of the distal humeral articular surface is required during surgery to treat fractures of the intercondylar humerus [5,18,25]. In our study, an examination of traverse sections of the distal triceps brachii revealed that the vessels and nerves that innervate the anconeus run downward in the triceps brachii and are relatively far from the intramuscular tendon.…”
Section: Discussionmentioning
confidence: 61%
“…It usually results in pain and dysfunction of the elbow joint. The common surgical treatment is open reduction and internal fixation, which requires adequate exposure of the distal humeral articular surface [5,18,25]. The typical surgical approach is osteotomy of the olecranon.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak bu avantajına rağmen, bahsedilen dezavantajları unutulmamalıdır. Sonuçta olekranon osteotomisi eklem içi bir osteotomidir ve sağladığı geniş görüş açısı nedeniyle AO-OTA Tip C distal humerus kırıklarının çoğunda tercih edilen yaklaşımdır (1).…”
Section: Discussionunclassified
“…Bununla birlikte cerrahi yaklaşımın seçimi; kırık biçimi, rehabilitasyon protokolleri ve cerrahi seçim dahil çok sayıda faktörü içerir (1). Bu girişimlerden posterior yaklaşım, humerus distal ucunun eklemi ilgilendiren ya da ekleme çok yakın kırık tiplerinin cerrahisi için oldukça popülerdir.…”
unclassified
“…그러나 상완골 원위부의 복잡한 해부학적 특성, 골절의 분쇄 및 골다공증으로 인하여 골절의 견고한 고정이 기술 적으로 어려워 합병증과 불량한 결과의 빈도가 높으며, 신 경 손상이나 이소성 골화 또는 기능 장애를 일으킬 수 있 다 7,17,19) . 상완골 원위부 골절의 AO 분류상 골절 유형에 따 라 Campbell의 후방 도달법과 경주두 도달법에 따른 수술적 접근법 및 운동 시작 시기에는 이견을 보이고 있다 15,16,22) . 저자들은 상완골 원위부 관절내 분쇄 골절에서 관혈적 정복 및 내고정 치료 시행 후 주관절의 기능 및 합병증을 수술접근법과 운동 시작시기, 골절 유형에 따라 후향적으 로 비교 분석하였다.…”
Section: 서 론unclassified